Deformation twinning in octahedron-based face-centered cubic metallic structures: Localized shear-force dipoles drive atomic displacements. (1st November 2022) - Gu, Hengfei; Liu, Chengze; Yuan, Fusen; Han, Fuzhou; Zhang, Yingdong; Ali, Muhammad; Guo, Wenbin; Ren, Jie; Zhang, Lifeng; Wu, Songquan; Li, Geping
Highlights: Monocrystalline (Fe, Nb)23 Zr6 nanoparticles (NPs) with an octahedron-motif-based Mn23 Th6 -type FCC structure were found to precipitate in a Zr-Nb-Fe alloy. Deformation twinning was successfully introduced in the (Fe, Nb)23 Zr6 NPs by cold work on the Zr-Nb-Fe alloy. The processing deformation twinning states were observed by high-resolution transmission electron microscopy (HRTEM) assisted by geometric phase analysis (GPA). A new zero-net-strain path for the <112>{111} deformation twinning in FCC structures was discovered. A loading criterion for deformation twinning of a FCC NP under uniaxial compression is proposed. Abstract: Twinning is found to impart favorable mechanical, physical and chemical properties to nanostructured materials. Deformation twinning prevails in face-centered cubic (FCC) nanocrystalline materials upon loading. In FCC structures, the <112>{111} deformation twinning is traditionally believed to nucleate and grow through layer-by-layer emission of 1/6<112> Shockley partial dislocations on consecutive {111} planes. We report that deformation twinning is able to occur in crystalline (Fe, Nb)23 Zr6 nanoparticles (NPs) that have a large Mn23 Th6 -type FCC structure with a Zr-octahedron as a motif. Based on direct atomic-scale observations, we discover a new zero-net-strain path for the <112>{111} deformation twinning in FCC structures. To form a [ 1 ¯ 1 ¯ 2]/(111) twin, for example, short ( 1 ¯ 1 ¯ 1) planes within two adjacent (111) plane layers in the repeated three-layer sequence of (111) planes are shear deformed continuously by a shear-force dipole along the [11 2 ¯ ] direction like a domino effect, whereas the other (111) plane in the repeated sequence remains intact. In addition, a loading criterion for deformation twinning of a FCC NP under uniaxial compression is proposed based on our observations. Our work here not only extends the fundamental understanding on deformation twinning in FCC structures, but also opens up studies of deformation behaviors in a class of Mn23 Th6 -type FCC materials. Graphical abstract: Image, graphical abstract